The complete mitogenome of Theloderma albopunctatum (Liu & Hu 1962) (Anura: Rhacophoridae) from the Karst areas of southwestern China - Jiang Yang; Ming-Le Mao; Cui-Pao He; Qiu-Yuan Lu; Chen-Rui Yan; Ning Xiao; Jiang Zhou (Mitochondrial DNA. Part B. Resources)
This study reports and characterizes the complete mitogenome of Theloderma albopunctatum. The mitogenome was 15,780 bp in length and contained 13 protein-coding genes, 22 transfer RNA genes, and two ribosomal RNA genes, with 29.35% A, 25.17% T, 14.24% G, and 31.24% C. The original data were assembled and annotated, and the complete mitochondrial genome was mapped. The phylogenetic tree obtained in this study supports the division of the Rhacophorinae and Buergeriinae subfamilies. This mitogenome provides a valuable resource for understanding evolutionary relationships within the Rhacophoridae family.